Uji Ketahanan Air Sediaan Breathable Nail Polish Ekstrak Ubi Jalar Ungu Dengan Variasi Eudragit® ® RL-100 - Wulandari, Asri; Fatmi, Mindya; Noerlaela, Ella; Sofiani, Alvina (Jurnal Fitofarmaka Indonesia, 2024)
AbstractThe use of nail polish on Muslim women is only allowed during menstruation and postpartum, because nail polish can block water from entering the nails, making ablution and prayer invalid. Conventional nail polish cannot penetrate water and air. Purple sweet potato peel extract contains anthocyanin as a colouring agent. The main composition in the manufacture of nail polish is a polymer that acts as a film forming material on the nails. Eudragit® RL-100 polymer used as a film-forming material that is permeable, can penetrate water, and air so that it can be used as a film forming material in breathable nail polish preparations. This study aims to formulate breathable nail polish preparations with variations of Eudragit® RL-100 as a polymer that can penetrate water and air based on the water resistance test. The formula was made in 3 variations with concentrations of Eudragit® RL-100 F1 (5%), F1 (10%), F2 (15%). The results showed that formula 2 is the best formula that meets the water absorption test using a 4.6% glass plate, absorption using a tissue 34 seconds, water penetration using effervescent tablets 11 seconds, and water absorption using simulated hand washing colour fading. Keywords: Eudragit® ® RL-10; breathable nail polish; polymer; water resistance; purple sweet potato skin extract.